2014
DOI: 10.1111/cod.12273
|View full text |Cite
|
Sign up to set email alerts
|

Copper hypersensitivity

Abstract: SummaryThe world production of copper is steadily increasing. Although humans are widely exposed to copper-containing items on the skin and mucosa, allergic reactions to copper are only infrequently reported. To review the chemistry, biology and accessible data to clarify the implications of copper hypersensitivity, a database search of PubMed was performed with the following terms: copper, dermatitis, allergic contact dermatitis, contact hypersensitivity, contact sensitization, contact allergy, patch test, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 84 publications
(95 reference statements)
0
27
1
Order By: Relevance
“…While Cu is an essential trace element for human health and an electron donor/acceptor for several key enzymes by altering redox states between Cu + and Cu 2+ [45], these properties can also cause cellular damage [17]. Its use as an antiviral agent is limited by allergic dermatitis [46], hypersensitivity [47], and multiorgan dysfunction [48].…”
Section: Discussionmentioning
confidence: 99%
“…While Cu is an essential trace element for human health and an electron donor/acceptor for several key enzymes by altering redox states between Cu + and Cu 2+ [45], these properties can also cause cellular damage [17]. Its use as an antiviral agent is limited by allergic dermatitis [46], hypersensitivity [47], and multiorgan dysfunction [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, data on dermal irritation by copper and its compounds are scant and the role of copper as an irritant/sensitizer remains controversial3. A recent review on copper hypersensitivity concluded that copper is a weak sensitizer as compared with other metallic compounds14. However, with the prevalence of skin permeation enhancement methods (such as microneedles and laser) used in cosmetic and pharmaceutical industry15, copper compounds may pose a higher risk to cause skin irritation, which necessitates a thorough skin toxicity testing.…”
mentioning
confidence: 99%
“…Cometa et al have shown that this activity is retained upon entrapment of the particles in a hydrogel [17], and similarly with conventional polymers [18]. The effective encapsulation of the copper may, furthermore, diminish possible dermatological problems arising through copper hypersensitivity [19,20].…”
Section: Introductionmentioning
confidence: 99%